2018
DOI: 10.2147/ijn.s166661
|View full text |Cite
|
Sign up to set email alerts
|

Micro-/nano-topography of selective laser melting titanium enhances adhesion and proliferation and regulates adhesion-related gene expressions of human gingival fibroblasts and human gingival epithelial cells

Abstract: BackgroundSelective laser melting (SLM) titanium is an ideal option to manufacture customized implants with suitable surface modification to improve its bioactivity. The peri-implant soft tissues form a protective tissue barrier for the underlying osseointegration. Therefore, original microrough SLM surfaces should be treated for favorable attachment of surrounding soft tissues.Material and methodsIn this study, anodic oxidation (AO) was applied on the microrough SLM titanium substrate to form TiO2 nanotube ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
76
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(81 citation statements)
references
References 45 publications
4
76
0
1
Order By: Relevance
“…Specimen Preparation and Treatment. The SLM specimens were manufactured as described previously [12,15]. Briefly, round-disk samples (diameter, 10 mm; thickness, 1 mm) were designed by SolidWorks® 12.0 (SolidWorks Corp, USA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Specimen Preparation and Treatment. The SLM specimens were manufactured as described previously [12,15]. Briefly, round-disk samples (diameter, 10 mm; thickness, 1 mm) were designed by SolidWorks® 12.0 (SolidWorks Corp, USA).…”
Section: Methodsmentioning
confidence: 99%
“…After SLM modifications both in vivo and in vitro (i.e., anodic oxidation, alkali-heat treatment, etc. ), remarkable antibacterial properties, bone regeneration, and soft tissue adhesion were demonstrated with an SLM surface [12,14,15]. However, few of them possess both biocompatibility and antibacterial activity at the same time.…”
Section: Introductionmentioning
confidence: 99%
“…Chitin particle uniform distributed over the membrane surface and did not make any is flat with minimal roughness. Some researchers have shown that rough surface has greater potential for cell adhesion that is principal for biocompatibility [22]. Just after material interacts with body fluids, protein absorbs onto the surface and plays a role of vesical substrate for cell adhesion.…”
Section: Resultsmentioning
confidence: 99%
“…The authors demonstrated that cell adhesion was significantly higher on machined and Ti-Unite surfaces than on the SLA implant surfaces. In another study using monolayer primary gingival fibroblasts and keratinocytes, Xu et al [ 47 ] reported that applying anodic oxidation on a micro-roughened, selective laser melted titanium surfaces, and subsequent calcium phosphate nanoparticle embedding resulted in enhanced bioactivity when compared to mechanical polishing. Perez-Diaz et al [ 48 ] demonstrated that the surface morphology of titanium can influence fibroblast cell adhesion and viability differentially and independently of the roughness parameters.…”
Section: Discussionmentioning
confidence: 99%